2009
DOI: 10.1111/j.1471-0528.2009.02279.x
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of labour in nulliparous women with an unfavourable cervix: a randomised controlled trial comparing double and single balloon catheters and PGE2 gel

Abstract: Objective To compare the efficacy and patient satisfaction of three methods of labour induction (double balloon catheters, single balloon catheters and prostaglandin gel) in term nulliparous women with unfavourable cervices.Design Randomised controlled trial.Population A total of 330 nulliparous women with unfavourable cervices induced at term.Methods Three cervical ripening study arms were used: double balloon catheter (107 women); 16F Foley catheter (110 women) and PGE 2 gel (2 mg) (113 women).Main outcome m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
176
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(207 citation statements)
references
References 25 publications
20
176
1
6
Order By: Relevance
“…The rate of LSCS in our study is agreeable. 16,19 There was no association of increased rate of cesarean section with the Foley's catheter PGE2 gel use.…”
Section: Resultsmentioning
confidence: 94%
“…The rate of LSCS in our study is agreeable. 16,19 There was no association of increased rate of cesarean section with the Foley's catheter PGE2 gel use.…”
Section: Resultsmentioning
confidence: 94%
“…6,9 There was no association of increased rate of cesarean section with the Foley's catheter PGE 2 gel use. 8,9 Fetal outcome data showed no significant difference between Group A and Group B with respect to birth wt (2.67 ± 0.44 and 2.58, / = 4.28, 3df, p = 0.188), MAS (8 and 10 respectively), 1 min Apgar score <7 (14 and 17 respectively), NICU admission rate (38 and 43 respectively). Thus the present study shows that the fetal outcome results were also comparable in both the groups.…”
Section: Resultsmentioning
confidence: 96%
“…However, most of the studies found higher rate of successful delivery after induction. The reason for which cesarean section was Mishanina et al [48] 2014 Systematic review and meta-analysis Decreased Hofmeyr and Gulmezoglu [92] 2001 Systematic review Decreased Wood et al [93] 2014 Meta-analysis Decreased Gulmezoglu et al [47] 2006 Systematic review Decreased Gulmezoglu et al [94] 2012 Systematic review Decreased Sanchez Ramos et al [29] 2003 Systematic review Decreased Alfirevic et al [76] 2014 Systematic review Decreased Alfirevic et al [95] 2000 Systematic review Decreased Boulvain et al [30] 2008 Systematic review Decreased Vogel et al [35] 2013 Systematic review Decreased Crowley [96] 2000 Systematic review No difference Boulvain et al [73] 2016 Systematic review Not clear Guerra et al [26] 2009 Secondary analysis Decreased Cheng [97] 2008 RCT Decreased Koopmans et al [98] 2009 RCT Decreased Pennel et al [99] 2009 RCT Increased Bhutto et al [100] 2013 RCT Nil Hermus et al [101] 2009 Cohort No difference Marry et al [37] 2015 Cohort Decreased Yeast et al [102] 1999 Cohort Decreased Nooh et al [103] 2005 Retrospective Decreased Dubline et al [19] 2000 Cohort Increased Johnson et al [104] 2003 Cohort Increased Verhoeven et al [22] 2012 Case control Increased…”
Section: Discussionmentioning
confidence: 99%